Transformación del Estadio Bellavista, de espacio deportivo a sistema público de soporte. - Ramos Aguilar, Freddy Steve (2023)
Currently, the city of Ambato has suffered a demographic growth that has accelerated urbanization processes, leaving aside the quality of public and private space. As a result, the quality of life of the inhabitants has been affected. In addition, several infrastructures have reached the end of their useful life, due to the years and the need to adapt to their urban transformation. The Bellavista stadium emerges as a fundamental piece of this change, its strategic location and its potential, represents a decisive role in the search for a sustainable Ambato. Based on solid, theoretically grounded ideas, it is imperative to generate strategies that allow for the connection, transformation and recovery of the Bellavista space. From an urban and architectural intervention at the macro, meso and micro levels, we seek to integrate a support system that meets the needs of the city and the Bellavista neighborhood, this includes promoting multimodal mobility without limitations for pedestrians, as well as paying attention to generating a green fabric that takes advantage of the transformed urban landscape and contributes to improving the quality of life of the people.